Psychometric Properties and the Cut-Off Point of the English Version of the Yatt Suicide Attitude Scale - Norhayati Ibrahim PhD; Normah Che Din PhD; Noh Amit PhD; Shazli E. Ghazali PhD; Aisyah Mohd Safien MEdu; Ching Sin Siau PhD (SAGE Publishing, 2022)
Background: The Malay version of the Yatt Suicide Attitude Scale (YSAS) was found to be reliable and valid for use in the Malaysian context. This study aims to validate and determine the cut-off points of the English version of the YSAS for a wider application by English-speaking researchers and practitioners. Methods: The English version of the YSAS, the Suicidal Behaviors Questionnaire-Revised (SBQ-R), and Kessler's K10 Psychological Distress Scale were distributed to 527 university students. Factor analysis was employed in the evaluation of its construct validity. The determination of the convergent and concurrent validity was determined by way of a bivariate correlation with the SBQ-R and Kessler's K10 scales. Cronbach's alpha and Receiver Operating Characteristic-analysis were also used to measure the internal consistency reliability as well as evaluate the screening properties of the scale. Results: The English YSAS and its ideation and attempt subdomains exhibited a high internal consistency value (>.8). The scale also had a cumulative variance of 76.39% and acceptable convergent and concurrent validity when compared to the SBQ-R and K10. The instrument demonstrated a better specificity in terms of the total score and suicide attempt and a better sensitivity trait on the suicidal ideation score. Conclusion: The English YSAS is a valid and reliable scale to assess suicidality, suicidal ideation, and suicide attempt among Malaysian university students.